2015
DOI: 10.1177/084456211504700106
|View full text |Cite
|
Sign up to set email alerts
|

Honouring Stories: Mi'kmaq Women's Experiences with Pap Screening in Eastern Canada

Abstract: Mi'kmaq women are reported to have lower rates of Papanicolaou (Pap) screening and higher rates of cervical cancer than non-Aboriginal women. This qualitative participatory study used postcolonial feminist perspectives and Indigenous principles to explore Mi'kmaq women's experiences with Pap screening within the contexts that shaped their experiences. Community facilitators assisted with the research process. Talking circles and individual in-depth interviews were conducted with 16 Mi'kmaq women. Also, health-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(50 citation statements)
references
References 22 publications
1
48
0
1
Order By: Relevance
“…Despite the many atrocities, Aboriginal cultural traditions and values have been preserved, and serve as testament to the resiliency of the people [43]. For example, in conducting research with Mi'kmaw women and Pap-smear screening [22] found that some women talked openly about Residential School's impact on their health. In some instances, women became angry and tearful.…”
Section: Research In Indigenous Women's Healthmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite the many atrocities, Aboriginal cultural traditions and values have been preserved, and serve as testament to the resiliency of the people [43]. For example, in conducting research with Mi'kmaw women and Pap-smear screening [22] found that some women talked openly about Residential School's impact on their health. In some instances, women became angry and tearful.…”
Section: Research In Indigenous Women's Healthmentioning
confidence: 99%
“…Research has shown that a lack of cultural safety and sensitivity when Aboriginal women are forced to seek information about healthcare from Western sources such as pamphlets and other print materials, which are not always representative or reflective of the women's realities [22]. In some instances, women receive culturally unsafe care because of the devaluing of Aboriginal knowledge, traditions, and cultural ways.…”
Section: Culturally Safe Practicesmentioning
confidence: 99%
See 2 more Smart Citations
“…Di samping itu, pendekatan tindakan penyertaan juga digunakan bagi penyelidikan yang meneroka isu-isu sosial dengan populasi yang terpinggir seperti orang asli (MacDonald, 2013). Aplikasi pendekatan tindakan penyertaan ini banyak melibatkan golongan belia dalam komuniti, pembangunan kemahiran kepimpinan dan pembangunan ilmu pengetahuan.…”
Section: Metodologi Kajianunclassified